A framework for grouping and read-across of nanomaterials- supporting innovation and risk assessment. (December 2020) - Stone, Vicki; Gottardo, Stefania; Bleeker, Eric A.J.; Braakhuis, Hedwig; Dekkers, Susan; Fernandes, Teresa; Haase, Andrea; Hunt, Neil; Hristozov, Danail; Jantunen, Paula; Jeliazkova, Nina; Johnston, Helinor; et al.
Graphical abstract: Highlights: The GRACIOUS Framework supports industrial and regulatory users to streamline innovation and risk assessment of nanomaterials. The GRACIOUS Framework guides users to identify the most appropriate hypothesis that defines how specific nanoforms can be grouped. Tailored Integrated Approaches to Testing and Assessment allow the user to gather evidence to test their grouping hypothesis. The GRACIOUS Framework combines outputs of the IATA into a data matrix to support risk decision making or risk assessment. Abstract: According to some legislation grouping can streamline data gap filling for the hazard assessment of substances. The GRACIOUS Framework aims to facilitate the application of grouping of nanomaterials or nanoforms (NFs), in a regulatory context and to support innovation. This includes using grouping to enable read-across from (a) source(s), for which data and information exist, to a similar target NF where information is lacking. The Framework provides an initial set of hypotheses for the grouping of NFs which take into account the identity and use(s) of the NFs, as well as the purpose of grouping. Initial collection of basic information allows selection of an appropriate pre-defined grouping hypothesis and a tailored Integrated Approach to Testing and Assessment (IATA), designed to generate new evidence to support acceptance or rejection of the hypothesis. Users needing to develop their own user-defined hypothesis (and IATA) are also supported by the Framework. In addition, the IATA guides acquisition of the information needed to support read-across. This approach gathers information to render risk assessment more efficient, affordable, as well as reducing the use of test animals.